Men at a gay information fair - Ted Sahl (photographer):::Creator::::::::::::
Photograph shows (left-to-right) Bill Welch, and Ross Parlette standing at the DIGNITY booth at the Lambda Association community information fair, 1980. Bill is handing a Ross a piece of paper. The sign behind them reads: "DIGNITY, mission valley gay Catholic men & women and their friends".